2016
DOI: 10.1227/neu.0000000000001389
|View full text |Cite
|
Sign up to set email alerts
|

Congress of Neurological Surgeons Systematic Review and Evidence-Based Guideline on Primary Management of Patients With Nonfunctioning Pituitary Adenomas

Abstract: NFPA, nonfunctioning pituitary adenoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 23 publications
0
54
1
Order By: Relevance
“…Based on the available clinical evidence, mainly retrospective and prospective observational cohort studies, pituitary surgery is the treatment of choice in symptomatic CNFPA patients and in those who show tumor growth during follow-up. Surgery is accompanied by a significant reduction in tumor size, and a significant improvement in both visual and pituitary functions [23]. It is note-worthy that in our series of incidental CNFPAs, a high percentage (42.1 %) was treated with surgery suggesting a high prevalence of non-perceived symptoms (neuroophtalmologic and/or endocrine symptoms) in these patients.…”
Section: Discussionmentioning
confidence: 63%
“…Based on the available clinical evidence, mainly retrospective and prospective observational cohort studies, pituitary surgery is the treatment of choice in symptomatic CNFPA patients and in those who show tumor growth during follow-up. Surgery is accompanied by a significant reduction in tumor size, and a significant improvement in both visual and pituitary functions [23]. It is note-worthy that in our series of incidental CNFPAs, a high percentage (42.1 %) was treated with surgery suggesting a high prevalence of non-perceived symptoms (neuroophtalmologic and/or endocrine symptoms) in these patients.…”
Section: Discussionmentioning
confidence: 63%
“…5 Nonfunctioning adenomas are those without any recognizable hormone production and may present clinically with vision loss or hypopituitarism. 6 A broad spectrum of visual symptoms has been reported in the literature, ranging from no alteration to blindness. 7 Visual impairment may comprise a decrease in visual acuity (41%), impaired color vision (56-71%), ocular movement alterations (8%), and visual field disturbances, the last one being the most common, with a reported prevalence from 37 to 96% in different studies.…”
Section: Introductionmentioning
confidence: 99%
“…Immediate tumour volume decrease was observed in nearly all patients with a residual tumour rate of 10-36% (Lucas et al 2016). Visual improvement is observed in 75-91% of patients, while 35-50% of patients display an improvement in hypopituitarism (Lucas et al 2016). It has been reported that a postoperative improvement in gonadal, thyroid and adrenal axes occurs in 64.9, 71.9 and 33.9% of cases, respectively (Nomikos et al 2004).…”
Section: Surgical Treatmentmentioning
confidence: 91%
“…TSS, when performed by an experienced surgeon, is a safe procedure with relatively low complication rates: a total resection is achieved in 60-73% of NFPitNETs (Yu et al 2018). Immediate tumour volume decrease was observed in nearly all patients with a residual tumour rate of 10-36% (Lucas et al 2016). Visual improvement is observed in 75-91% of patients, while 35-50% of patients display an improvement in hypopituitarism (Lucas et al 2016).…”
Section: Surgical Treatmentmentioning
confidence: 96%